Enhanced Silica Removal by Polyamine‐ and Polyacrylamide‐Polyaluminum Hybrid Coagulants. Issue 11 (14th October 2015) - Miranda, Ruben; Latour, Isabel; Hörsken, Arne; Jarabo, Rocío; Blanco, Angeles
Abstract: Silica removal is the main bottleneck for a high reuse of deinking paper mill effluents due to silica scaling on the reverse‐osmosis units generally used. The efficiency of inorganic‐organic hybrid coagulants formed by the combination of polyaluminum nitrate sulfate (PANS) with different dosages of cationic polyacrylamide (PAM) or polyamines (PA) on silica removal is analyzed. These hybrids significantly increased the silica and chemical oxygen demand (COD) removal at all pH values studied, with PA modification being the most efficient. While conventional aluminum coagulants allow high silica removal, only at both high pH and dosages the PA derivatives achieve high silica and soluble COD removal without pH adjustment. PAM hybrids only slightly improved the efficiency of PANS at the highest active contents. Abstract : A high reuse of deinking paper mill effluents depends on successful silica removal. Formulations of hybrid coagulants based on the combination of an aluminum salt with polyacrylamide and polaymines are significantly more efficient than the base aluminum salts. They allow higher silica and chemical oxygen demand removals at considerably lower dosages without the need of pH regulation.